2013
DOI: 10.2527/jas.2012-5702
|View full text |Cite
|
Sign up to set email alerts
|

Influence of dietary fiber type and amount on energy and nutrient digestibility, fecal characteristics, and fecal fermentative end-product concentrations in captive exotic felids fed a raw beef-based diet

Abstract: Little nutritional or metabolic information has been collected from captive exotic cats fed raw diets. In particular, fiber types and concentrations for use in raw meat-based diets for captive exotic felids have not been well studied. Our objective was to evaluate the effects of fiber type and concentration on apparent total tract energy and macronutrient digestibility, fecal characteristics, and fecal fermentative end-products in captive exotic felids. Four animals of each captive exotic species (jaguar (Pant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
26
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 20 publications
(34 citation statements)
references
References 37 publications
7
26
1
Order By: Relevance
“…From the results of this experiment and earlier reports, it is seems that supplementation of JA may favorably modulate the hindgut micro‐biota of Indian leopard fed a meat‐on‐bone diet. A comparison with the fecal microbial profiles of other felids would indicate that the concentration of coliformes and Clostridium spp., as observed in this study, was similar to those reported in other felids [Vester et al, ; Kerr et al, ]. Research conducted earlier have indicated that the concentrations of Lactobacillus species were higher in cheetah, jaguar, Malayan tiger, and Siberian tiger fed a horse meat based diet as compared to those fed a beef‐based diet.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…From the results of this experiment and earlier reports, it is seems that supplementation of JA may favorably modulate the hindgut micro‐biota of Indian leopard fed a meat‐on‐bone diet. A comparison with the fecal microbial profiles of other felids would indicate that the concentration of coliformes and Clostridium spp., as observed in this study, was similar to those reported in other felids [Vester et al, ; Kerr et al, ]. Research conducted earlier have indicated that the concentrations of Lactobacillus species were higher in cheetah, jaguar, Malayan tiger, and Siberian tiger fed a horse meat based diet as compared to those fed a beef‐based diet.…”
Section: Discussionsupporting
confidence: 92%
“…The apparent digestibility of CP ranged from 84.6 to 87.8% (mean 86.8 ± 0.19), which was within the range of 83.1–89.7% reported in captive leopard [Barbiers et al, ]. However, apparent digestibility of CP was higher (90–97%) in felids fed meat trimmings or muscle meat [Kerr et al, ]. Lower apparent digestibility of CP as observed in this study in leopards could be attributed to higher content of bones, ligaments and tendons in meat‐on bone as compared to muscle meat.…”
Section: Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…Research in exotic felids has focused on diets with components that are easily digestible (i.e., raw meat) with little attention paid to animal and plant dietary fibers [Clauss et al, ]. Apparent total tract digestibility was high for all diets (OM digestibility >85%); however, apparent total tract macronutrient digestibilities by cats fed Ground in this study were the highest and within the ranges reported previously for cats fed raw diets [Vester et al, ; Kerr et al, ]. Of the few studies in the literature pertaining to raw diets, evidence for increased digestibility of raw versus extruded diets exists in sand cats [Crissey et al, ] and African wildcats [Vester et al, ].…”
Section: Discussionsupporting
confidence: 77%
“…Apparent total tract CP digestibility was low for cats fed Extruded. Inclusion of fermentable fiber has been reported to decrease apparent total tract CP digestibility dietary fiber source [Kienzle et al, ; Sunvold et al, ; Vester et al, ; Kerr et al, ]. The Extruded contained beet pulp, a moderately fermentable fiber source, while Canned contained cellulose, a low fermentable fiber.…”
Section: Discussionmentioning
confidence: 99%